(untitled) (Journal of the College of Basic Education, 2022)
Many scholars and researchers have paid attention to the concept of psychological stress through the importance of this concept. And its impact on the players from a scientific, mental and psychological point of view, as well as the emotions that lead to many Sometimes to psychological pressures before participating in competitions. Psychological stress is considered one of the important factors in the occurrence of stress and excessive emotion in the individual.